Juridical Instruments for Drinking Water Management through a Village Owned Business Agency in Apuan Village, Susut District, Bangli District - Ida Ayu Putu Widiati; Ni Made Puspasutari Ujianti; Luh Putu Suryani; Putu Sandiawan Putra Wiranata; Ida Bagus Gede Sesana Dharma (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The responsibility of the State in ensuring the fulfillment of the people's right to drinking water is carried out through the implementation of the Drinking Water Supply System (SPAM), one of which can be implemented by BUM Desa. The problems to be studied are: What is the legal form of BUM Desa in drinking water management in Apuan Village? and what efforts are made by the BUMDes of Apuan Village in optimizing drinking water management? This research is empirical legal research with a sociology of law approach. The results of the study indicate that the legal form of the Apuan Village BUM must be renewed through a conversion process so that it is a legal entity and reorganizes the drinking water management business unit so that it has legality in drinking water management. In the context of optimizing drinking water management, a legal instrument is needed in the form of the Apuan Village Regulation on the Drinking Water Management System based on the SDA Law and the SPAM PP to ensure certainty of the quality, quantity, and continuity of SPAM for the Apuan Village community. Furthermore, it is necessary to prepare SPM and SOP, monitoring facilities, as well as human resource development for drinking water management through comparative studies and training or mentoring.